Analysis of Charismatic Leadership Style Implementation by School Principals in Enhancing Teacher Performance and Professionalism: A Study of 61 Elementary Schools - Tihazanah; Putra, Mulia; Sari, Siti Mayang (Jurnal Komunikasi Pendidikan, 2024)
Effective school leadership is critical for enhancing teacher performance and professionalism. This research aims to analyze the application of the school principal's charismatic leadership style in improving teacher performance and professionalism at an elementary school in Indonesia. Employing a descriptive qualitative research design, this study systematically explores the unique traits and behaviors of charismatic leaders, including their strong charm, self-confidence, clear vision, and ability to inspire followers. While charismatic leadership positively impacts values, ideology, and participation, it can also lead to a focus on personal loyalty and the use of power for personal gain. The success of charismatic leadership is evidenced by the close relationship between leaders and followers, with followers showing high commitment to the leader's vision. This study contributes to the education field by providing insights into how charismatic leadership can be harnessed to improve teacher performance and professionalism, highlighting both its benefits and potential drawbacks.